Individualized targeting of the posterior parietal cortex with intermittent theta burst stimulation in anorexia nervosa: a randomized, double-blind, sham-controlled protocol - Meregalli, Valentina; Gentili, Sofia; Menardi, Arianna; Vallesi, Antonino; Olivo, Daniele; Manara, Renzo; Serino, Andrea; Risso, Gaia; Sambataro, Fabio; Favaro, Angela; Collantoni, Enrico (Frontiers in Neuroscience, 2026)
BackgroundAnorexia nervosa (AN) is a severe psychiatric disorder frequently marked by poor treatment response and chronic progression toward rigid, restrictive behaviors. These features highlight the need for innovative strategies targeting core mechanisms and symptoms of the disorder. This feasibility trial evaluates individualized intermittent theta-burst stimulation (iTBS) of the posterior parietal cortex (PPC) as an adjunct to treatment-as-usual, with the goal of identifying patient-specific targets and paving the way for personalized neuromodulation in AN.MethodsThirty-four adults with AN (≥18 years, illness ≥12 months, ≥1 prior unsuccessful treatment) will be randomized (1:1) to 20 sessions of real or sham iTBS over 4 weeks. Stimulation will be delivered with a MagPro system and a Cool B70 A/P active/sham coil; motor threshold will be estimated with the Stochastic Approximator (SAMT) and re-checked weekly. Individualized stimulation target will be defined based on resting state functional magnetic resonance imaging data to identify the cortical region within the PPC that is maximally functionally connected with the activity of two meta-analytically derived networks representing body representation and implicit behavioral tendencies. Coil placement will be neuronavigated on individual T1 magnetic resonance imaging (MRI). Assessments will take place at baseline (T0), post-treatment (T1), and 4-month follow-up (T2), covering clinical status (body mass index (BMI), psychopathology, and quality of life), experimental tasks (implicit body representation, peripersonal space, approach–avoidance tendencies toward food, interoceptive accuracy, and neurocognitive functioning), and MRI. Feasibility endpoints include recruitment, retention, completion, blinding, and tolerability. Ethics approval: 6168/EST/25; registration: NCT07106645.DiscussionThis trial emphasizes individualized PPC targeting and rigorous motor threshold (MT) estimation to advance personalized neuromodulation in AN. Feasibility and effect-size data will guide a confirmatory randomized clinical trial, while mechanistic analyses will test whether targeted iTBS strengthens body-schema circuits and aligns neural changes with clinical improvement, supporting a precision-psychiatry approach to eating disorders.Trail registrationhttps://clinicaltrials.gov/study/NCT07106645, identifier NCT07106645.